Families of Adults with Autism : Stories and Advice for the Next Generation. - Johnson, Jane, 1966- (Jessica Kingsley Publishers, 2008)
Families of Adults with Autism is a collection of real-life stories of people on the autism spectrum growing up, as told by their parents and siblings. The individual accounts explore the challenges that families of people with autism have faced, and the techniques they have used to improve the quality of their children's lives, from mega-doses of vitamins and dietary changes to intensive interaction. The contributors also relate how they have worked with their children or siblings to help them to function at their highest possible level, be it showing an awareness of their environment, holdin.